(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to investigate the counseling services provided to gifted students in the Al-Baha region from their point of view, and to identify the differences in these views according to the students ’gender, educational stages, and the cities in which they study. The descriptive survey approach was followed in its relevance to the research objectives. Likewise, a random sample of gifted elementary, intermediate, and secondary school students was selected by the method of stratified sampling, as the sample reached (175) male and female students. The instrument of the research consisted of the questionnaire of counseling services presented to gifted students from their point of view prepared by researchers. The results showed that the level of counseling services from the students ’point of view was high, and the third dimension (the general framework for the care and regulation of behavior and attendance) came first with a very high degree. It was followed by the twelfth dimension (enhancing intellectual security) and with a very high degree. Then, the seventh dimension (List of problems) came to be with a high degree. It was followed by the first dimension (supervising the attendance and departure of students) with a high degree; followed by the fifth dimension (caring for outstanding students) with a high degree, followed by the sixth dimension (the Behavioral Excellence Award) with a high degree, followed by the eighth dimension (communication between home The school and documenting the relationship between them) with a high degree, followed by the eleventh dimension (preparing students for school tests, abilities, and achievement) with a high degree, followed by the fourth dimension (developing students’ behavioral and intellectual skills) with a high degree, followed by the ninth dimension (preserving public property) with a high degree, followed by the dimension ten (educational and vocational counseling programs) with a high degree, while the second dimension came in last place (extension and educational applications of growth characteristics), as well as with a high degree. The results also indicated that there were no statistically significant differences in the views of gifted students about the counseling services provided to them in terms of gender, educational stages, and the cities in which they study. In light of the results, the researchers recommended a set of recommendations and suggestions.